Strengthening Qur’anic Memorisation through The Halaqah Method in Non-Formal Islamic Education - Muhammad Nur Ilham Ilahi; Surahman Amin; Hermanto Hermanto (JIE (Journal of Islamic Education), 2026)
The limited number of empirical studies on Qur'anic memorisation strengthening practices in non-formal Islamic educational institutions in Eastern Indonesia, particularly in Sorong, Southwest Papua. This indicates the need for research on structured tahfiz learning methods. This study aims to analyse the implementation stages of the halaqah method, the role of murabbi in the tahfiz learning process, as well as the impacts and challenges of strengthening Qur'anic memorisation at Rumah Qur'an Zona Qur'an 1, Sorong. This study employed a descriptive qualitative approach with a case-study design. This study collected data through participant observation of halaqah activities, semi-structured interviews with two murabbi and sixteen students, and documentation, including memorisation records, institutional data, and learning activities. This study analysed the data using the Miles and Huberman interactive model, which comprises data reduction, data display, and conclusion drawing and verification. This study strengthened data validity through source, technique, and time triangulation. The findings show that halaqah functions as a structured, collective, corrective, and motivational system for strengthening Qur'anic memorisation. Its main stages include opening and motivation, muraja’ah, ziyadah, tasmi’, direct correction, evaluation, and closing prayer. The murabbi acts as an academic mentor, motivator, evaluator, and moral exemplar. The method improves discipline, recitation quality, self-confidence, peer support, and memorisation consistency. However, several challenges remain, including differences in students' abilities, limited time, fatigue, and uneven parental support. This study provides contextual contributions from Sorong, a region that remains underrepresented in halaqah and tahfiz studies. It offers a practical model for strengthening Qur'anic memorisation through guided feedback, positive reinforcement, and collaborative learning.